Reflections on CPoS: A Journey Across Five Decades - Kreyenfeld, Michaela (Comparative population studies, 2025)
In this editorial, Michaela Kreyenfeld, former board member, author and reviewer, reflects on her own experiences with and the evolution and significance of Comparative Population Studies (CPoS), formerly Zeitschrift für Bevölkerungswissenschaft (ZfB), highlighting its role as a dedicated, rigorous platform for demographic and population research. CPoS embraces core demographic topics as well as interdisciplinary approaches, exemplified for example by seminal works on fertility, demographic transitions, and sociological theory. Valued for fairness, accessibility, and intellectual integrity, CPoS offers a respected venue for both emerging and established scholars. * This article belongs to a series celebrating the journal's 50th anniversary.